Acoustic modeling of honeycomb structures for second load direction with damping consideration. Issue 2 (June 2022) - Saffar, Saber
The control of low-frequency noise in buildings has become a critical issue because of the inadequate sound insulation in low frequencies (<200 Hz) for most partitions and doors. In the present study, an analytical model has been proposed to specify the relationship between the acoustic parameters such as acoustic impedance of honeycomb and the honeycomb geometry. In this regards, three materials (Polycarbonate, Polypropylene, and Polyurethane), seven angles (45°, 30°, 15°, 0°, −15°, −30°, −45°), and three cell arrangement (1 × 1, 2 × 2, and 3 × 3) were considered to find out the effect of these parameters on the sound absorption coefficient. Sound absorption in the frequency range of 1–500 Hz for angles of 45°, 30°, 15°, 0°, −15°, −30°, −45° was demonstrated using MATLAB software. A comparison of the results showed that the greater the angle's absolute value, the more the sound absorption coefficient. By comparing all three materials' absorption coefficient values, it was concluded that the 1 × 1 arrangement had greater absorption than the 2 × 2 and 3 × 3 arrangements. Also, the number of resonance peaks of polyurethane material for all angles was greater than the others in the same frequency range. Then, the panel with the honeycomb core of Polyurethane and 1 × 1 arrangement was recommended for cells with an internal angle of −45° in the present research case study for having more sound absorption.